Penerapan Teori Permainan dalam Menentukan Strategi Pemasaran Optimum pada Produk Mi Instan (Mie Sedaap, Gaga, dan Supermi) di Lingkungan Mahasiswa Matematika Universitas Sumatera Utara - Miftah Khairani; Muhammad Romi Syahputra; Parapat Gultom; Mardiningsih Mardiningsih (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Instant noodle consumption in Indonesia has continued to increase in the last few years, which indicates that there are more business opportunities for instant noodle products in Indonesia. Proved by the number of instant noodle brands scattered on the market. This has led to increased competition among companies in order to be the best in the eyes of consumers. Marketing strategies are needed to win competition as well as increase sales, ranging from taste innovations, prices, product quality, promotions, and so on. In this study, game theory is used to investigate the competition between Mie Sedaap, Gaga, and Supermi. Using pure strategy is obtained game value that shows that the optimal strategy for Mie Sedaap is ease of purchase, the optimum strategy for Gaga is packaging strategy, and the optimum strategy for Supermi is price strategy.